The Concept of the Classical Sharia Market: A Socio-Legal Historical Analysis - Agus Miswanto; Syamsul Anwar; Siti Fatimah (CV. RADJA PUBLIKA, 2026)
This article examines the concept of the Classical Sharia Market through a socio-legal historical approach by analyzing the transformation of market systems from the pre-Islamic period to the establishment of the Market of Medina under Prophet Muhammad (peace be upon him). The study addresses the contemporary tendency to separate Islamic economic theory from its historical and institutional foundations. This research aims to analyze the characteristics of pre-Islamic markets, identify the normative principles underlying the classical Sharia Market, and reconstruct its relevance for contemporary economic challenges. Employing a qualitative socio-legal historical method, the study integrates historiographical analysis with normative examination of Qur’anic and Hadith sources related to muamalah using Lawrence Friedman’s framework of legal structure, substance, and legal culture. The findings reveal that Islam did not abolish existing market mechanisms but reformed them through ethical and institutional regulations grounded in justice, transparency, and social welfare. The Market of Medina emerged as an open-access and tax-free market supervised through the institution of al-hisbah, while prohibiting exploitative practices such as riba, gharar, and maysir. The study concludes that the Classical Sharia Market represents an integrated socio-legal economic system that harmonizes market freedom, ethical governance, and social justice. This article contributes to the development of Islamic economic studies by offering a historical and conceptual reconstruction of the Sharia Market as a relevant framework for contemporary Islamic economic development.